An Alternative Approach to the Institutional Economics of the Eurozone Crisis. Issue 1 (2nd January 2016) - Engel, Sascha
Abstract: I argue that the Eurozone crisis is neither a crisis of European sovereigns in the sense of governmental over-borrowing, nor a crisis of sovereign debt market over-lending. Rather, it is a function of the "sovereign debt market" institution itself. Crisis, I argue, is not an occurrence, but an element fulfilling a precise technical function within this institution. It ensures the possibility of designating — in the market's day-to-day mechanisms rather than analytical hindsight — normal (tranquil, undisturbed) market functioning. To show this, I propose an alternative view on the institutional economics of sovereign debt markets. First, I engage literature on the emergent qualities of the institutions "market" and "firm" in product markets, concluding that the point of coalescence for markets is the approximation of an optimal observation of consumer tastes. I then examine the specific institution "financial markets, " where the optimal observation of economic fundamentals is decisive. For the specific sub-institution "sovereign debt market, " I conclude that the fundamentals in question — country fundamentals — oscillate between a status of observable fundamentals outside of markets and operationalized fundamentals influenced by market movements. This, in turn, allows me to argue that the specific case of the Eurozone crisis is due to neither of the two causes mentioned above. Rather, the notion of "crisis" takes on a technical sense within the market structure, guaranteeing the separation of herd behavior and isomorphic behavior on European sovereign debt markets. By the same token, the so-called Eurozone crisis ceases to be a crisis in the conventional sense.